Transcriptome Analysis Reveals Genes Responsive to Three Low-Temperature Treatments in Arabidopsis thaliana - Bricia Ruiz-Aguilar; Natalia B. Torres-Serrallonga; María Azucena Ortega-Amaro; Arianna Duque-Ortiz; Cesaré Ovando-Vázquez; Juan Francisco Jiménez-Bremont (Plants)
Cold stress impedes the growth and development of plants, restricts the geographical distribution of plant species, and impacts crop productivity. In this study, we analyzed the Arabidopsis thaliana transcriptome to identify differentially expressed genes (DEGs) in 14-day-old plantlets exposed to temperatures of 0 °C, 4 °C, and 10 °C for 24 h, compared to the 22 °C control group. Among the top 50 cold-induced genes at each temperature, we identified 31 genes that were common across all three low temperatures, with nine genes common to 0–4 °C, eight genes to 4–10 °C, and two genes to 0–10 °C. Using q-RTPCR, we analyzed selected genes at 24, 48, and 72 h under the three low temperatures. Our data revealed that genes, such as galactinol synthase 3 (Gols3, At1g09350), CIR1 (At5g37260), DnaJ (At1g71000), and At5g05220 (unknown function), exhibited the highest expressions at 0 °C and 4 °C throughout all time points. We also studied genes from the UDP-glycosyltransferase (UGT78) family, including At5g17030 (D3), At5g17040 (D4), At5g17050 (D2), and At1g30530 (D1), which showed increased expression at low temperatures compared to plantlets at 22 °C for 24 h. Gene ontology analysis revealed that DEGs highly enriched were found in biological processes such as “RNA secondary structure unwinding” and “rRNA processing” induced at the three low temperatures, whereas processes related to photosynthesis were repressed. Our findings indicated upregulation in the expression of four RNA helicases (RH13, RH48, RH32, and RH29), belonging to the “RNA secondary structure unwinding” category, mainly at 0 °C and 4 °C. This study provides valuable information on the molecular mechanisms that activate Arabidopsis thaliana in its early response to these three low temperatures.